2012
DOI: 10.1016/j.jacc.2012.01.077
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorenal Syndrome Type 1

Abstract: Cardiorenal syndrome (CRS) type 1 is characterized as the development of acute kidney injury (AKI) and dysfunction in the patient with acute cardiac illness, most commonly acute decompensated heart failure (ADHF). There is evidence in the literature supporting multiple pathophysiological mechanisms operating simultaneously and sequentially to result in the clinical syndrome characterized by a rise in serum creatinine, oliguria, diuretic resistance, and in many cases, worsening of ADHF symptoms. The milieu of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
146
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 341 publications
(149 citation statements)
references
References 111 publications
1
146
0
2
Order By: Relevance
“…When kidney function is normal, the contrast medium is excreted relatively quickly (within a few hours); however, in patients with chronic kidney disease, the excretion half‐life might be more than 10 hours 29. In addition, excessive hydration may increase risk of heart failure, consequently leading to volume overload or increased preload, lower cardiac output, and inadequate renal perfusion, such as cardiorenal syndrome, which, in turn, may increase venous pressure, leading to kidney congestion, activation of the renin angiotensin aldosterone system, and marked alterations of immune and somatic cell signaling 30, 31. These are likely the reasons that higher hydration volumes at the average speed did not show any benefits in preventing CI‐AKI in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…When kidney function is normal, the contrast medium is excreted relatively quickly (within a few hours); however, in patients with chronic kidney disease, the excretion half‐life might be more than 10 hours 29. In addition, excessive hydration may increase risk of heart failure, consequently leading to volume overload or increased preload, lower cardiac output, and inadequate renal perfusion, such as cardiorenal syndrome, which, in turn, may increase venous pressure, leading to kidney congestion, activation of the renin angiotensin aldosterone system, and marked alterations of immune and somatic cell signaling 30, 31. These are likely the reasons that higher hydration volumes at the average speed did not show any benefits in preventing CI‐AKI in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,5 The main underlying mechanism is thought to be related to plasma volume reduction (PVR) with the subsequent reduction of renal perfusion and activation of the renin-angiotensin-aldosterone system. 6 Previous studies have shown that PVR, represented by hemoconcentration, is associated with WRF. 7,8 Therefore, the maintenance of optimal PV without the resultant impairment of renal function is essential for AHF management.…”
Section: Clinical Perspective On P 532mentioning
confidence: 98%
“…The acute cardiorenal syndrome (type 1), defined as a worsening of renal function in patients with acutely decompensated heart failure, arises in 25-33% of patients with ADCHF (20). To determine the appropriate treatment, patients with this syndrome should be classified on pathophysiologic grounds as suffering from either prerenal renal failure with predominant left-heart failure (forward failure) or intrarenal renal failure due to renal venous congestion (backward failure) (20,21).…”
Section: Oxygen Administration and Non-invasive Vs Invasive Ventilationmentioning
confidence: 99%